Governance Issues for SMEs - Clarke , Thomas; Klettner , Alice (Journal of Law and Governance, 2009)
This paper draws on research into the corporate governance practices of small and medium enterprises (SMEs) listed on the Australian Securities Exchange. Interviews were conducted with the directors and/or company secretaries of 19 SMEs. The aim of the research was to explore not only SME corporate governance structures and processes but how SMEs had chosen to implement the Principles and the reasons for their choices. The paper addresses the issue of whether the ASX Corporate Governance Principles and Recommendations were appropriate for SMEs. It describes the SME responses to the requirements, how these differ from those of larger companies, and how these differences impact on small companies.